De-extremization Effort through Political Re-education Camps In China: A Case of Uyghur Ethnic Minorities - Nagib, Rima Abdul Mujib; Anam, Syaiful (Faculty of Economics and Social Science, Department of International Relations, Universitas Amikom Yogyakarta, 2021)
The rise of Islamic extremism has prompted global Islamophobia and general hatred for Muslims, which is felt towards both the religion itself and ethno-religious groups such as the one present in China. The spread and acts of Islamic extremism in China might surprise the global community but the concerning level of threat on the issue affected domestic security policies. In explaining the case study, the qualitative research uses a combination of descriptive and explanatory approaches while simultaneously merging the three constructivist theory approaches from notable scholars such as Alexander Wendt, Martha Finnemore and Peter Katzenstein. The research concludes that while there may be variations of methods to combat Islamic extremism, the implementation of political re-education camp for the Uyghurs seems to be the best and most effective method in both de-extremizing the minority group from potential Islamic extremist ideology and enforcing the Chinese government’s interests. Justifications of the choice include the constructivist aspects of the international norms, repetition of historical and existing trajectories as well as the successful rate of cleansing troubled and infected people from negative ideologies based on the Chinese societal norms.